2011
DOI: 10.1186/1752-153x-5-49
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for environmentally friendly chemical peptide synthesis in water using water-dispersible amino acid nanoparticles

Abstract: Due to the vast importance of peptides in biological processes, there is an escalating need for synthetic peptides to be used in a wide variety of applications. However, the consumption of organic solvent is extremely large in chemical peptide syntheses because of the multiple condensation steps in organic solvents. That is, the current synthesis method is not environmentally friendly. From the viewpoint of green sustainable chemistry, we focused on developing an organic solvent-free synthetic method using wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…3 Triangular-shaped and spherical-shaped gold nanoparticles have been used for detection of DNA and as an immunoassay system for antibodies. 4 The use of nanoparticles as potential drug carriers in the treatment of cancer has also been reported. Nanoparticles can be prepared using a variety of chemicals and physical methods, including chemical reduction, [5][6][7] photochemical reduction, [8][9][10][11] electrochemical reduction, 12,13 and heat vaporization.…”
Section: Introductionmentioning
confidence: 99%
“…3 Triangular-shaped and spherical-shaped gold nanoparticles have been used for detection of DNA and as an immunoassay system for antibodies. 4 The use of nanoparticles as potential drug carriers in the treatment of cancer has also been reported. Nanoparticles can be prepared using a variety of chemicals and physical methods, including chemical reduction, [5][6][7] photochemical reduction, [8][9][10][11] electrochemical reduction, 12,13 and heat vaporization.…”
Section: Introductionmentioning
confidence: 99%
“…The development of synthesis methods that do not use organic solvents would be desirable (Anastas and Warner 1998;Winterton 2001;Sheldon 2007). In recent years, we have been driven to focus on the development of a method for peptide synthesis in water which is an environmentally friendly solvent (Hojo et al 2001(Hojo et al , 2004a(Hojo et al , b, 2007(Hojo et al , 2008(Hojo et al , 2011(Hojo et al , 2012(Hojo et al , 2013. Solid-phase peptide synthesis (SPPS) is commonly performed via a base-labile 9-fluorenylmethoxycarbonyl (Fmoc) strategy.…”
Section: Introductionmentioning
confidence: 98%
“…It must also be mentioned that Hojo and co-workers demonstrated that the dispersed nanoparticles can be easily removed from the aqueous waste stream, through filtration or ultracentrifugation. Subsequent publications by Hojo and co-workers have also gone on to demonstrate the application of similar water-dispersible Boc-nanoparticles, as well as the use of efficient microwave heating to reduce coupling times from 1 h to 3 min [22,23].…”
Section: Fmoc-and Boc-protected Nanoparticlesmentioning
confidence: 99%